2017
DOI: 10.1371/journal.pone.0176774
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiological survey of bacteremia by multidrug resistant Pseudomonas aeruginosa: the relevance of intrinsic resistance mechanisms

Abstract: The bacterial factors associated with bacteremia by multidrug-resistant and extensively drug-resistant P. aeruginosa, including overexpression of efflux pumps, AmpC overproduction, and loss/alteration of the OprD porin in isolates that are non-Metallo-β-Lactamase producing were analyzed in a retrospective study. Molecular analyses included strain typing by Pulsed Field Gel Electrophoresis and identification of key genes via qualitative and quantitative PCR-based assays. Previous use of carbapenems and tracheos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
12
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 53 publications
6
12
0
5
Order By: Relevance
“…39 Although the MexXY-OprM system is known as a substantial element in aminoglycoside resistance in only P. aeruginosa, 40 it is also over-expressed in multi-drug resistant P. aeruginosa 41 and similar reports to our study have shown its over-expression in carbapenemresistant P. aeruginosa strains. 7,42,43 MexAB-OprM over-expression was observed in 21.8% of the isolates, concurring with Xavier and co-workers. 44 In contrast, Dantas et al 7 and Chalhoub et al 32 reported a much higher frequency of MexAB-OprM over-expression in P. aeruginosa isolates.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…39 Although the MexXY-OprM system is known as a substantial element in aminoglycoside resistance in only P. aeruginosa, 40 it is also over-expressed in multi-drug resistant P. aeruginosa 41 and similar reports to our study have shown its over-expression in carbapenemresistant P. aeruginosa strains. 7,42,43 MexAB-OprM over-expression was observed in 21.8% of the isolates, concurring with Xavier and co-workers. 44 In contrast, Dantas et al 7 and Chalhoub et al 32 reported a much higher frequency of MexAB-OprM over-expression in P. aeruginosa isolates.…”
Section: Discussionsupporting
confidence: 87%
“…Downregulation of oprD generally causes resistance to imipenem and meropenem. 7 Another major mechanism of Carbapenem resistance in P. aeruginosa is decreasing the antibiotic concentration through efflux systems belonging to the resistance-nodulation-division (RND) family (MexAB-OprM, MexCD-OprJ, MexEF-OprN, MexXY-OprM, MexJK and MexVW). 8 Meropenem is affected by high regulation of MexAB-OprM, MexCD-OprJ, and MexXY-OprM, whilst imipenem is not affected.…”
Section: Introductionmentioning
confidence: 99%
“…This high consumption of antimicrobials results in a higher incidence of resistant bacteria [4]. The rate of carbapenem resistance differs in distinct geographic regions.…”
Section: Discussionmentioning
confidence: 99%
“…The P. aeruginosa porin OprD is a substrate-specific porin that facilitates the diffusion of basic amino acids, small peptides, and carbapenems into the cell. OprD mediated resistance occurs as a result of decreased transcriptional expression of oprD and/or function mutations that disrupt protein activity [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Geralmente em países de baixa e média renda, como o Brasil, diferentes fatores podem levar a emergência e disseminação de clones resistentes, especialmente nas UTIs. Entre alguns desses fatores estão a alta densidade de uso de antibióticos, que resultam frequentemente na pressão seletiva que favorece a emergência de cepas resistentes e multirresistentes, adicionada a existência de clones dominantes e falhas nas práticas básicas de prevenção e controle de infecções, que podem em parte justificar a disseminação desses micro-organismos no ambiente hospitalar (DANTAS et al, 2017). O HC-UFU apresenta todas essas características proporcionando ambiente ideal para a disseminação de clones de alto risco.…”
Section: Comitê De éTicaunclassified